A Review of Patch Array Antenna on Millimeter Wave Wireless Communication in 5G Application in advance computing - Kumar Allemki, Voladari Praveen kumar, Dr Giriraj Kumar Prajapati, Dr.Santhosh (International Journal of Advanced Science and Technology, 2020)
A millimeter wave rectangular microstrip fix antenna array for fifth generation correspondences (5G) applications is introduced. With the expansion popular for high information rates and limit, there is a need to incorporate mm-Wave frequencies for 5G. The 4×2 fix array is mimicked and manufactured on  a Rogers RT/Duroid 5880 substrate with a thickness of 0.25 mm. The impacts of bowing the substrate on the antenna execution are additionally exhibited. The exploratory outcomes demonstrate a fragmentary data transmission and addition of over 3% and 16.1 dBi, separately.. In this paper, we display the motivation for future radio wire for 5G remote specialized, approach, and offer an arrangement of reenactment comes about that show 2.7 GHz recurrence can be used while using steerable directional antenna. The proposed idea is executed by using IE3D test system